Longitudinal effects of home-based HIV self-testing on well-being and health empowerment among men who have sex with men (MSM) in the United States. Issue 2 (1st February 2020) - Wray, Tyler B.; Chan, Philip A.; Simpanen, Erik M.
ABSTRACT: HIV self-test (HST) kits have been available for purchase directly by consumers since 2012. However, public health and prevention programs have been slow to adopt self-testing as a strategy for improving testing rates and regularity, in part due to concerns about its effects on the well-being of users and lack of follow-up. This study explored whether there were differences in several constructs related to well-being, including health-related quality of life, social support, health empowerment, and emotional distress, across those who used HSTs versus tested at a clinic over time. Data were drawn from a longitudinal randomized controlled trial exploring methods of encouraging HIV testing (clinic-based, regular home delivery of HSTs) and providing follow-up afterward. Results showed that using HST in a given month was not associated with changes in either distress or well-being that same month. Although social support was lower in months when HST was used (versus clinic-based testing), participants reported that engaging in other health behaviors (e.g., Healthy diet, exercise) were more important in months they used HST compared to testing in a clinic, suggesting that HST may empower MSM to begin making other lifestyle changes that could improve their health. Trial registration: Uniform Trial Number identifier: NCT02876926.